Analisis HAM Terhadap Mekanisme Perlindungan Pihak Ketiga Dalam RUU Perampasan Aset - Sulaiman Kurdi; Jam'ul Ihsan Bambang; Ahmad Rizkhan Nurullah (El-Dusturie, 2025)
Abstract: The Draft Bill on Asset Forfeiture as an instrument to combat corruption and economic crimes raises new problems when linked to human rights (HR). One of the main issues is the weak protection for third parties who are not directly involved in the criminal act but are potentially harmed by the asset forfeiture mechanism. To date, there is no specific legislation that comprehensively regulates the protection of third parties in court proceedings under the Draft Bill on Asset Forfeiture. This study employs a normative juridical method with statutory and conceptual approaches, focusing on the rights of third parties that are often neglected, including potential violations of the rights to property, justice, and legal certainty. As emphasized in Law No. 39 of 1999 on Human Rights, third parties should be guaranteed human rights protection encompassing the right to property, legal certainty, and fair treatment before the law. However, the provisions in the Draft Bill on Asset Forfeiture are not fully aligned with these principles. The mechanisms of objection and opposition available to third parties remain limited and tend to be procedural, as third parties are still burdened with proving the legality of their ownership, while compensation is restricted to the value of the seized assets. Therefore, this study highlights the urgency of strengthening third-party protection norms from a human rights perspective, so that asset forfeiture instruments are not only effective in combating crimes but also consistent with the rule of law and substantive justice.   Keywords: Human Rights; Third-Party Protection; Asset Forfeiture Bill; Legal Certainty; Rule of Law   Abstrak:RUU Perampasan Aset sebagai instrumen pemberantasan tindak pidana korupsi dan kejahatan ekonomi menimbulkan problematika baru ketika dikaitkan dengan hak asasi manusia (HAM). Salah satu permasalahan utama adalah lemahnya perlindungan terhadap pihak ketiga yang tidak terkait langsung dengan tindak pidana, namun berpotensi dirugikan oleh mekanisme perampasan aset. Hingga kini belum terdapat peraturan perundang-undangan khusus yang secara komprehensif mengatur perlindungan pihak ketiga dalam persidangan pada Draft RUU Perampasan Aset. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual, dengan fokus pada kajian hak-hak pihak ketiga yang sering terabaikan. Sebagaimana dijelaskan dalam UU No. 39 Tahun 1999, seharusnya pihak ketiga tetap memperoleh perlindungan hak asasi yang meliputi hak atas kepemilikan, kepastian hukum, dan perlindungan yang adil di depan hukum. Namun, kondisi yang ditemukan dalam Draft RUU Perampasan Aset belum sepenuhnya sejalan dengan prinsip-prinsip tersebut. Mekanisme keberatan dan perlawanan yang diberikan kepada pihak ketiga masih terbatas dan cenderung prosedural, di mana pihak ketiga tetap dibebani pembuktian bahwa aset yang disita merupakan miliknya yang sah, sementara ganti kerugian dibatasi pada nilai aset. Oleh karena itu, penelitian ini menegaskan penguatan norma perlindungan pihak ketiga dalam perspektif HAM,agar instrumen perampasan aset tidak hanya efektif sebagai sarana pemberantasan kejahatan, tetapi juga sejalan dengan keadilan substantif. Kata Kunci: Hak Asasi Manusia; Perlindungan Pihak Ketiga; RUU Perampasan Aset; Kepastian Hukum; Negara Hukum